PHYSICAL ACTIVITY LEVEL DURING PANDEMIC – A PILOT STUDY - Ioan Niculaie NEGRU; István BALOGA; András ÁLMOS (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2020)
The aim of our study was to find out about physical activity level, during this pandemic period. Nowadays the entire society is affected, by this pandemic, socially, economically and sport activities as well. According to our data, people from this sample have a high level of physical activity, but they declared to have a lower fitness level reported to previous years.